2013
DOI: 10.1111/nph.12244
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for recent evolution of cold tolerance in grasses suggests current distribution is not limited by (low) temperature

Abstract: SummaryTemperature is considered an important determinant of biodiversity distribution patterns. Grasses (Poaceae) occupy among the warmest and coldest environments on earth but the role of cold tolerance evolution in generating this distribution is understudied.We studied cold tolerance of Danthonioideae (c. 280 species), a major constituent of the austral temperate grass flora. We determined differences in cold tolerance among species from different continents grown in a common winter garden and assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 60 publications
6
40
0
Order By: Relevance
“…Although climate is commonly considered the major determinant of species distribution, it may well be that other biotic and abiotic factors confound the link between a specific climate parameter and the fundamental niche (Soberon & Arroyo‐Peña, ). A study of the realized niche of cold tolerance in the southern temperate grass subfamily Danthonioideae indeed underestimated the fundamental niche (Humphreys & Linder, ). However, Humphreys and Linder () also showed that species experiencing cold temperatures in their native range showed a higher survival rate in a growth experiment of overwintering capacity, indicating a close correlation between realized niche and physical tolerance to frost.…”
Section: Discussionmentioning
confidence: 99%
“…Although climate is commonly considered the major determinant of species distribution, it may well be that other biotic and abiotic factors confound the link between a specific climate parameter and the fundamental niche (Soberon & Arroyo‐Peña, ). A study of the realized niche of cold tolerance in the southern temperate grass subfamily Danthonioideae indeed underestimated the fundamental niche (Humphreys & Linder, ). However, Humphreys and Linder () also showed that species experiencing cold temperatures in their native range showed a higher survival rate in a growth experiment of overwintering capacity, indicating a close correlation between realized niche and physical tolerance to frost.…”
Section: Discussionmentioning
confidence: 99%
“…) but only to a limited extent because no clear relation between cold tolerance evolution and the distribution range has been established (Skálová et al . ; Humphreys & Linder ). Through evolutionary history, more angiosperms have radiated into freezing environments through three key cold tolerance mechanisms: decreasing the hydraulic conduit diameter, becoming deciduous and shortening their life form (Zanne et al .…”
Section: Introductionmentioning
confidence: 99%
“…). However, the current understanding of this evolutionary mechanism is insufficient to explain the rapid cold differentiation that is observed among plant populations (Humphreys & Linder ; Leiblein‐Wild et al . ; Zanne et al .…”
Section: Introductionmentioning
confidence: 99%
“…Despite its tropical origins, a few grass clades have successfully diversified in temperate environments Humphreys and Linder, 2013). In particular, the diversification of Pooideae grasses in the northern hemisphere coincides with a period of major global cooling that peaked during the Eocene-Oligocene boundary 34 to 33.5 million years ago (Zachos et al, 2001;Mannion et al, 2014).…”
mentioning
confidence: 99%